Effects of Oceanfeed Swine Feed Additive on Performance of Sows and Their Offspring - L. Del Tuffo; F. Laskoski; C. M. Vier; M. D. Tokach; S. S. Dritz; J. C. Woodworth; J. M. DeRouchey; R. D. Goodband; L. A. Constance; M. Niederwerder; E. Arkfeldt (Kansas Agricultural Experiment Station Research Reports, 2019)
The objective of this study was to evaluate the effects of the Oceanfeed SwineTMfeed additive on sows and their offspring performance. Oceanfeed Swine is a product created by drying and blending a selected mix of brown, red, and green seaweeds (Ocean Harvest Technology, Galway, Ireland). A total of 28 sows (DNA 241, DNA Genetics, Columbus, NE) and litters were used from d 30 of gestation until weaning (d 20 of lactation). Treatments consisted of providing a control diet (n = 14 sows) or the Oceanfeed Swine diet (n = 14 sows) added at 0.5% of complete diet in gestation and 0.66% in lactation diets. Then offspring of these sows were used for the nursery and grow-finish portions of the study. In the nursery, a total of 360 weanling pigs (DNA 241 × 600), were used in a 56-d trial. There were 5 pigs per pen and 18 replications per treatment. Treatments were arranged in a split-plot design with sow treatment (control vs. Oceanfeed Swine diet) as a whole-plot and nursery treatment (control vs. Oceanfeed Swine diet) as the sub-plot. In the nursery phase, the Oceanfeed Swine was added at 0.75% of the diet. During the nursery phase, fecal scoring was used to categorize fecal consistency and fecal samples were collected for microbial analysis. At the end of the nursery portion, pigs from two nursery pens within weight block and treatment were combined and moved to the finishing barn with approximately 10 pigs per pen and 9 replications per treatment. Pigs were weighed weekly (nursery) or every two weeks (finisher) to determine growth performance. At the conclusion of the finishing phase, all pigs were marketed for carcass data collection. The addition of the Oceanfeed Swine in sow diets during gestation and lactation did not influence (P>0.10) sow body weight (BW) at the end of gestation or at weaning. Also, there were no differences in colostrum yield, colostrum and milk composition, or litter performance between the two treatments during the lactation period. In the nursery, there was no evidence for the effect of sow by nursery treatment, interactions (P>0.10) observed. For the overall nursery period (weaning to day 56), no sow or nursery effects were observed for growth performance. For fecal scores, there was a sow × nursery treatment interaction (P<0.062) observed. In general, pigs weaned from control sows then fed the control diet, or pigs weaned from Oceanfeed Swine sows and fed Oceanfeed Swine had firmer fecal scores than the other two combinations. There was also a sow treatment by day interaction (P<0.007) observed with pigs weaned from control sows initially (day 7) having firmer feces than those weaned from sows fed Oceanfeed Swine in the nursery. However, by day 21, there appeared to be no differences in fecal consistency among pigs weaned from either sow treatment group. For microbial analysis, there was a marginally significant increase in the proportion of pigs with the families Peptostreptococcaceae and Veillonellaceae detected in the pigs from sows fed Oceanfeed Swine diets and fed Oceanfeed Swine compared with the control group (P= 0.085). Moreover, pigs from sows that were fed Oceanfeed Swine diet and then fed Oceanfeed Swine had an increased (P= 0.048) mean number of species detected within the family Ruminococcaceae and had a marginally significant increased (P= 0.076) mean number of species detected within the family Lachnospiraceae, two families that are generally considered beneficial. Finally, pigs from sows that were fed Oceanfeed Swine diets, then fed Oceanfeed Swine had marginally significant lower (P= 0.069) mean number of species detected within the family Fusobacteriaceae, a family that is generally considered pathogenic. In the finishing period, a sow by finishing treatment interaction (P= 0.061) was observed for F/G from d 0 to 55 after weaning. Pigs weaned from sows fed control diets and switched to Oceanfeed Swine in the nursery or pigs weaned from sows fed Oceanfeed Swine then fed control diets in the finishing phase had improved F/G compared with the two other treatment combinations. No evidence for any main effect differences (P>0.10) was observed on overall growth performance. However, sow by finishing treatment interaction (P= 0.059) was observed for backfat depth. This inter- action was similar to the day 0 to 55 F/G response. Pigs weaned from sows fed control diets and then fed control diets in the nursery/finishing period had greater backfat depth and decreased percentage lean compared with other treatment combinations (sow treatment×nursery/finishing treatment interaction (P<0.073)). In summary, the addition of Oceanfeed Swine in gestation, lactation, and the nursery/finishing phases had no consistent effect on sow or litter performance. However, a shift in the microbiota was observed in the pigs from sows fed Oceanfeed Swine diet, then fed Oceanfeed Swine with higher number of species detected within Ruminoccocaceae and Lachnospiraceae families that are generally considered beneficial and lower number of species within the family Fusobacteriaceae that is normally considered pathogenic.
Keywords: microbiome; pigs; seaweed